(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The article analyzes word acquisition as a complex process. In the process of analysis, it was found that although borrowed words appear as a pattern and are the object of research of the lexicology department, the spiritual and content filling of this pattern is associated with various social, political, and cultural factors. In fact, language is a social phenomenon, and no change in it occurs without the participation of society, we have distinguished the attempts of the state and society to make drastic changes to the language as a non-linguistic factor, and the gradual adaptation of phonetic, lexical, and grammatical adaptation of the word acquisitions to their own language pattern over time as a linguistic phenomenon.